ANALISIS PRILAKU KRIMINALITAS DALAM NOVEL PULANG PERGI KARYA TERE LIYE : TINJAUAN SOSIOLOGI SASTRA - Fira Arfiliana; Elsa Mulya Karlina (CV. ADIBA ASIHA AMIRA, 2026)
This study aims to uncover and describe the forms of criminal behavior and their contributing factors in the novel Pulang Pergi by Tere Liye. As a literary work rich in action and intrigue, this novel reflects the complexity of modern crime. This research is a qualitative study using content analysis methods through the lens of sociology of literature and criminological theory. The research data consists of a textual corpus (words, phrases, sentences, dialogues, and narratives) indicating criminal acts, sourced from Tere Liye's novel Pulang Pergi (SabakGrip Publisher, 2021). Data collection techniques employed include bibliography, reading-observation, and note-taking. The results show two main findings: first, the forms of criminal behavior in the novel are dominated by transnational organized crime and white-collar crime, manifesting in extreme violence, murder, smuggling of illegal commodities, bribery, and money laundering within the shadow economy ecosystem. Second, the triggers of criminality include motives for power/economic dominance, the influence of a social environment that normalizes crime (differential association), and cycles of revenge between families of shadow rulers. Through this depiction, Tere Liye delivers a sharp social criticism regarding the fragility of law enforcement in the face of global capitalism and covert political power.